IMMANUEL TUTORIAL SERVICE OF ANUGERAH STUDY COURSE IN RAWACANA - Oce Datu Appulembang; Kurnia P.S. Dirgantoro; Jacob Stevy Seleky; Novel Priatna (Jurnal Sinergitas PKM & CSR, 2017)
The low standart of living in scavenger area in Rawacana is affect children education in their family. Most of them are only get a modest education and even do not have the opportunity to get an education and drop out. Bu Honey and family have a desire to increase the standart of living of this community through education for local children. He has set up study huts in the scavenger area to help children get the informal education. Seeing the number of children who need to be educated in that place, so that they need the educators who are committed to teach in that place. Therefore, cooperation with Mathematics Education, FIP TC UPH facilitated by her husband as UPH lecturer Mr. Dylmoon through Community Service acrivity. The Mathematics Education Study Program provides educators as a tutor. They will help to teach the children in that study lodge every week. The purpose of this activity is to help children in their homework, to help understand the difficult lessons, to help children in installing a striving attitude through study hard and to reach out the children who do not get formal education in school so that they can experience the same education as those who attend school.